1995
DOI: 10.1212/wnl.45.6.1155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term treatment with antiepileptic drugs on serum lipid levels in children with epilepsy

Abstract: We determined serum levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), and triglycerides (TGs) in 125 healthy children and in 119 children with epilepsy who had been receiving carbamazepine (58 children), phenobarbital (22 children), or valproic acid (39 children) for 7 months to 10.5 years (mean, 5.8 years). None of the variables considered was significantly correlated with time elapsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
91
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 0 publications
10
91
1
1
Order By: Relevance
“…see refs. [131][132][133][134][135][136]) whereas other studies failed to detect a significant correlation between phenobarbital treatment and changes in lipid levels (e.g. see ref.…”
Section: Experimental and Clinical Observationsmentioning
confidence: 99%
“…see refs. [131][132][133][134][135][136]) whereas other studies failed to detect a significant correlation between phenobarbital treatment and changes in lipid levels (e.g. see ref.…”
Section: Experimental and Clinical Observationsmentioning
confidence: 99%
“…In contrast, few studies reported that CBZ therapy does not affect serum lipids (TG, TC, HDL-c, LDL-c, and VLDL-c) (113). Lower values of TC, TG, HDL-c, and LDL-c similar to healthy controls have been found in epileptic patients receiving VPA, a well-known enzyme inhibitor (6,110). Gender difference has been demonstrated with significant increase of HDL among women and higher LDL-c and TG but lower HDL-c in men that are independent to the dose or plasma concentrations of CBZ.…”
Section: B) Lipid and Lipoprotein Metabolism In Epileptics Differentimentioning
confidence: 95%
“…The tendency to have recurrent, unprovoked seizures occurs with a prevalence of about 0.5% and a cumulative lifetime prevalence of 3% (1). Many studies have demonstrated that prolonged treatment with antiepileptic drugs (AEDs) could have some undesirable metabolic side effects including elevated plasma concentration of homocysteine (Hcy) (2 -4) and altered serum levels of cholesterol, lipoproteins (5,6), and uric acid (7). These findings have important clinical relevance to vascular endothelial dysfunction and atherosclerosis-related diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenobarbital is an antiepileptic known to induce hepatic microsomal enzymes. Microsomal enzyme induction with exogenous drugs can alter the metabolism of bile acids, bilirubin, total cholesterol (TC), triglyceride (TG), and other endogenous molecules [1,2]. A 10-month-old infant presented with hyperlipidemia due to rectal phenobarbital-paracetamol combination (Paranox ® ), which was used by the parents to reduce fever related to enterovirus infection.…”
Section: Introductionmentioning
confidence: 99%